A modified dentine infection model with fluorescent lipopolysaccharide and lipopolysaccharides sampling technique to compare XP-Endo finisher and passive ultrasonic irrigation - Alfirdous, Rayyan A.; Alquiria, Theeb A.; Jacinto, Rogerio C. [UNESP]; Martinho, Frederico C. (Wiley, 2022)
Aim: The lipopolysaccharides-dentine-infection (LPS-dentine-infection) models and sampling techniques frequently used to evaluate LPS disinfection have limitations. In this study, a LPS-dentine-infection model was devised using fluorescent conjugate LPS. Secondly, a sampling technique using cryogenic grinding for intraradicular LPS analysis was evaluated. Thirdly, the effectiveness of the XP-endo Finisher (XP-EF) was compared with passive ultrasonic irrigation (PUI) in removing LPS from root canal system. Methodology: Sixty-nine mandibular premolars were submitted to dentine pretreatment and inoculated with fluorescent LPS conjugate (Alexa Fluor® 594). Twenty-three teeth were analysed under confocal laser scanning microscopy (CLSM) to validate this modified LPS-dentine-infection model. Forty-six teeth were randomly divided into two experimental groups: XP-EF (n = 23) and PUI (n = 23). All teeth were instrumented with XP-endo shaper (XPS; FKG Dentaire) and 2.5% NaOCl. The root canals were sampled with paper points before (s1) and after (s2) instrumentation and after supplemental treatment (s3) with XP-EF and PUI. After s3, all roots were cryogenically ground for intraradicular LPS analysis (s4). Limulus amebocyte lysate assay was used for LPS quantification. The Friedman test was used for differences in LPS among four time-points (s1, s2, s3, and s4). Dunn's test was used for pairwise testing of time-points. The significance level was set at 5% (p <.05). Results: Fluorescent LPS conjugate was detected in 100% of the samples under CLSM with a penetration depth of approximately 400 μm into dentine. Chemo-mechanical preparation using XPS files significantly reduced LPS levels (p <.05). Both the XPS and PUI improved the LPS disinfection (p <.05), with no difference between them (p >.05). LPS was recovered from all samples after cryogenic grinding. The residual amount of LPS detected using the cryogenically sampling technique at s4 was approximately three times greater than with the paper-point sampling technique at s3. Conclusion: This study established a modified LPS-dentine-infection model using fluorescent conjugate LPS, and validated a LPS sampling technique for using cryopulverization intraradicular LPS analysis. Moreover, both the XP-EF and PUI further improved LPS disinfection from the root canals, and the innovative XP-EF was as effective as PUI.
Keywords: bacteria; disinfection; LPS; root canal; XP-endo finisher